1992
DOI: 10.1017/s0022215100121310
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis of the parotid gland: clinically indistinguishable from a neoplasm

Abstract: Tuberculosis of the parotid gland may be clinically indistinguishable from a neoplasm. This poses a problem with regard to management, because the treatment of tuberculosis is medical, whilst that of the majority of tumours is surgical. If radical surgery with resection of a branch or branches of the facial nerve is embarked upon in a patient with tuberculosis, without prior histological diagnosis, unnecessary permanent disability will result. Two cases of tuberculosis of the parotid gland are reported, demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 8 publications
0
11
0
2
Order By: Relevance
“…The clinical appearance may mimic parotitis or a parotid tumor. [1][2][3] The existence of a known parotid lesion, with or without enlarged cervical lymph nodes and with no history or other evidence of TB, was suggestive of a malignancy. Patients may therefore be referred for surgical intervention, which apparently carries risks of destruction of the parotid gland with fistula formation or facial palsy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical appearance may mimic parotitis or a parotid tumor. [1][2][3] The existence of a known parotid lesion, with or without enlarged cervical lymph nodes and with no history or other evidence of TB, was suggestive of a malignancy. Patients may therefore be referred for surgical intervention, which apparently carries risks of destruction of the parotid gland with fistula formation or facial palsy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients may therefore be referred for surgical intervention, which apparently carries risks of destruction of the parotid gland with fistula formation or facial palsy. [3][4][5][6] In a review of 216 surgeries for parotid tumors, Suoglu et al 1 found 6 patients (2.8%) with parotid TB. If presurgical evaluation can exclude the possibility of a tumor, the condition can be managed properly with medical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical exploration could lead to permanent facial nerve damage, gland destruction, fistula formation [9] and was deferred due to the negative consent given by the parents.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of M. tuberculosis from the biopsied parotid gland confirmed tuberculous parotitis. In MEDLINE,there are a considerable number of recent reports on tuberculous parotitis (2,3). These consecutive cases of myownrenewed the old knowledge, that tuberculosis truly is a multi-organ disease.…”
mentioning
confidence: 99%